Labeling for allergen: an evaluation of labels marked with the presence or absence of gluten and their risks inherent toceliac health in Brazil (Research, Society and Development, 2020)
Celiac disease (CD) is not considered a food allergy, it is an autoimmune disease characterized by an inflammatory process that involves the mucosa of the small intestine, due to the ingestion of gluten, thus reducing the absorption of essential nutrients for the good functioning of the organism. The only known treatment is a gluten-free diet, adopted for life and must be rigorous, complete, balanced and varied. However, in Brazil, we still find labeling errors, a serious circumstance, and the label is the way the celiac finds to protect himself from gluten and if there is an error, he will be induced to ingest the toxic antigen, causing his illness and causing injuries serious bodily injuries. Therefore, the objective of this study is to evaluate, through a literature review, the panorama of food labeling for celiac in Brazil. The databases of SCIELO, ANVISA, Ministry of Health, FENACELBRA, ASBAI, ACELBRA, MEDLINE, Google Scholar, and books were used as a research source, between November and March 2020. Therefore, the research confirmed that the legislation should be sufficient to promote alignment in the communication between the industry and the consumer and that Health Surveillance carries out interventions to eliminate, reduce or prevent risks, however, it is observed that corrective actions are still necessary so that patients with CD have access to safe food and that they can trust the words expressed on the packaging labels.